Multidisciplinary Community Care: Integrating Health Assistants, Pharmacists, Emergency Medical Services Technicians, Healthcare And Hospital Management Specialists, And Anesthesia Technicians For Patient Safety (The Review of Diabetic Studies, 2025)
BackgroundMedical errors and suboptimal care in community settings contribute significantly to global morbidity, with over 12 million adverse effects from medical treatment in 2021 alone. Fragmented silos in primary care, home health, and ambulatory services exacerbate risks like falls, medication discrepancies, and diagnostic delays, particularly for chronic disease patients. This review synthesizes multidisciplinary community-level strategies to enhance integration, safety, and quality using frameworks like the Rainbow Model of Integrated Care and Swiss Cheese Model.​MethodsA narrative synthesis of randomized trials, quasi-experimental studies, and scoping reviews evaluated GP-inclusive multidisciplinary teams (MDTs) across micro (home visits), meso (organizational), and macro (policy) levels. Outcomes assessed included healthcare utilization, functional status, satisfaction, and mortality. Integration enablers like shared digital records and strategies for falls prevention and medication safety were mapped.​ResultsMDTs reduced hospital utilization by up to 50%, improved physical functioning, and lowered adverse events through pharmacist-led reconciliation, nurse home assessments, and social worker navigation of non-clinical barriers. Equity improved via SDOH interventions, with cost savings from prevented readmissions and efficiencies in value-based models.​ConclusionsMultidisciplinary community approaches dismantle silos, fostering patient-centered safety via technology, policy reforms, and dashboards. Policymakers should prioritize funding, training, and metrics for scalable implementation to optimize care quality amid rising chronic burdens.